PENERAPAN KOMPRES TEPID WATER SPONGE TERHADAP PERUBAHAN SUHU TUBUH PADA ANAK USIA TODDLER 1-3 TAHUN YANG MENGALAMI HIPERTERMI AKIBAT DENGUE HEMORAGIC FEVER (DHF) DI RUANG MELATI RUMAH SAKIT TK.II DUSTIRA - Heliani Aprian, Lianie; Sarwendah, Endah; Zulva, Siti (Yayasan Putra Sukamanah Sejahtera, 2024)
Dengue Hemorhagic Fever (DHF) is a disease caused by the dengue virus transmitted by the Aedes aegypti mosquito. The main problem of DHF sufferers is hyperthermia, Hyperthermia is an increase in body temperature related to the body's inability to dissipate heat. Fever treatment can be done with tepid water sponge compresses, Giving tepid water sponge is more effective in lowering the child's body temperature because the use of this technique will accelerate the vasodilation of capillary blood vessels throughout the body so that the evaporation of heat from the skin to the surrounding environment will be faster. The purpose of this study is to identify before and after the application of Tepid Water Sponge in toddler children aged 1-3 years with Hyperthermia problems due to Dengue Hemorragic Fever (DHF). The case study descriptive method, with data collection techniques through the nursing care process. Data collection was carried out 1 intervention a day for 15 minutes. The results of the study obtained a body temperature of 38.9°C in patients after the application of tepid water sponge compresses, a decrease in body temperature of 38°C was obtained, there was a decrease in body temperature of 0.9°C. So it can be concluded that tepid water sponge therapy has an effect on lowering body temperature in children who experience hyperthermia due to Dengue Hemorragic Fiver (DHF). The recommendations that the author applies to families in order to be able to apply the water sponge compress technique in daily life, especially for patients suffering from DHF to intervene independently.